2004
DOI: 10.3928/0098-9134-20040601-07
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Basics: Effects of the Eden Alternative Model on Quality of Life Issues

Abstract: In Life Worth Living, Thomas (1996) proposed that in long-term care facilities for elderly individuals, loneliness, helplessness, and boredom are out of control and are steadily decaying the residents' spirits, adversely affecting quality of life. While Thomas' contention appeals to common sense, no empirical evidence is offered in its support. The purpose of this quasi-experimental study was to assess the impact of implementation of the Eden Alternative model on levels of loneliness, boredom, and helplessness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
85
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 15 publications
0
85
0
Order By: Relevance
“…32,36 Outcomes related to mood were measured in 7 studies with significant benefits in the homelike settings relative to traditional NHs in 2 of the 3 Eden Alternative studies that examined this outcome. 46,48 There was no significant difference in the third Eden Alternative study. 44 Findings were mixed relative to traditional NHs in the one study of nondementia-specific small house settings 45 and in 1 of the 3 dementia-specific settings that examined this outcome.…”
Section: Psychosocial Outcomesmentioning
confidence: 91%
See 1 more Smart Citation
“…32,36 Outcomes related to mood were measured in 7 studies with significant benefits in the homelike settings relative to traditional NHs in 2 of the 3 Eden Alternative studies that examined this outcome. 46,48 There was no significant difference in the third Eden Alternative study. 44 Findings were mixed relative to traditional NHs in the one study of nondementia-specific small house settings 45 and in 1 of the 3 dementia-specific settings that examined this outcome.…”
Section: Psychosocial Outcomesmentioning
confidence: 91%
“…42 Outcomes related to social activities/activation were measured in 3 Eden Alternative settings with significant beneficial effects relative to comparison NHs in one study, 44 no difference in one study, 43 and mixed findings in one study. 46 Kane et al 45 reported a positive effect of the Green House in relation to one comparison NH but not the other. In the 2 studies in dementia-specific settings, social activity/ activation outcomes were significantly better than in the comparison NHs.…”
Section: Psychosocial Outcomesmentioning
confidence: 97%
“…As for the resident outcomes, studies showed a decrease in boredom, helplessness, and depres-sion by improving residents' social relationships, growing plants or animals, or involving the residents in care decision-making [5]. The small-scale nursing homes (NHs) have also improved residents' quality of life by allowing residents to have more comfortable and individualized care [6].…”
Section: Introductionmentioning
confidence: 99%
“…To help rectify the difficulties associated with institutional living, a movement in long-term care called culture change focuses on a revolution in long-term care settings to create environments where the residents are at home; family members enjoy visiting; employees are respected and appreciated, and their opinions valued; quality of care is excellent; life is worth living; and legal action is unnecessary (Bergman, 2004;Rabig, Williams, Kane, Cutler, & McAlilly, 2006;Zimmerman & Cohen, 2010). Associated with the culture change movement is the need to adequately measure outcomes such as well-being (Kane, 2003).…”
Section: Introductionmentioning
confidence: 99%